Pemberdayaan Anak Melalui Program Bahasa Inggris, Melukis, PHBS, dan Gizi Bersama Pertukaran Mahasiswa Modul Nusantara Universitas Sumatera Utara - Ameilia Zuliyanti Siregar; Titien Indriyanti; Alisa Faith Kurniawan; Maulana Alfian Rizki Ananda; Nathasia Corrina Chandra (Universitas Negeri Semarang, 2023)
English learning program, Art Painting Therapy: Painting on a Totebag, Introduction to Clean and Healthy Living Behavior (CHLB) and a healthy balanced nutrition lifestyle were programs carried out as a social contribution of Archipelago Module Programme (AMP).The objectives of society was to increase awareness of speaking English, channeling positive emotions and childrenâ€™s creativity, freeing children to express themselves and preventing children from illness in the framework of forming the 2030-2040 golden generation. This activity uses demonstration methods and hands-on practice and combines audio-visual media with kinesthetic learning styles. The target of this activity to developedÂ childrens on Pimpinan Street, Medan Tembung. develop children's enthusiasm, self-potential, interests and talents in learning English and the arts. AMP's social contribution activities produce a culture of work ethic, empathy and sympathy for educational issues, especially developing motivation, enthusiasm and focus in learning for children in the city of Medan.